1‐(7‐Chloro‐1, 4‐dihydroquinolin‐4‐ylidene)thiosemicarbazide and its hydrochloride: evidence for the existence of a stable imine tautomer in the solid state of 4‐aminoquinoline free bases, an anomalous case in nitrogen heterocycles. Issue 7 (15th June 2015) - Machado, Rafael C.; Grazul, Richard M.; Diniz, Renata
<x xml:space="preserve">Abstract</x> In the solid state, crystals of both 1‐(7‐chloro‐1, 4‐dihydroquinolin‐4‐ylidene)thiosemicarbazide–methanol–water (2/1/1), 2C10H9ClN4S·CH3OH·H2O, (I), and its hydrochloride salt {systematic name: [(7‐chloro‐1, 4‐dihydroquinolin‐4‐ylidene)azaniumyl]thiourea chloride}, C10H10ClN4S+·Cl−, (II), assume the imine tautomeric form, contrary to other 4‐amino‐7‐chloroquinolines. Of particular interest are the N—C bond lengths, which have appreciable double‐bond character, and the C—N—C aromatic ring bond angle. Both of these parameters have been studied extensively in 4‐amino‐substituted quinolines. The crystal structures of (I) and (II) in this study provide interesting examples of the amino–imino tautomerism which exists in this class of compound and is, to the best of our knowledge, hitherto unreported.